Student needs in e-book use for academic presentation: A perspective on higher education - Nur Ilma Ambo; Masnih Mustapa (Quantum Academic, 2025)
Digital transformation in higher education has changed the methods of managing and delivering academic information, including the documentation and presentation of scientific training. This study analyzes students' needs regarding the use of eBooks as a documentation tool for scientific presentation in the context of higher education in the digital era. This study uses a needs analysis method and technology acceptance models like the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) to look at what makes eBooks acceptable and useful. The results of the literature synthesis and conceptual analysis found that students' needs for eBooks encompass four main dimensions: technical, pedagogical, socio-cultural, and economic. From a technical aspect, accessibility, usability, and the interoperability of eBooks with the university's academic system become critical factors. The pedagogical dimension emphasizes the potential of eBooks in enhancing interactive and collaborative learning experiences. From a sociocultural perspective, academic norms, peer influence, and digital literacy play important roles in the acceptance of this technology. Meanwhile, economic aspects and digital infrastructure determine the accessibility and sustainability of eBook usage in higher education institutions. This study proposes a conceptual model of students' needs for eBooks that connects these four dimensions as a basis for improving academic policies and developing more user-friendly eBooks. The implications of this study also include recommendations for stakeholders in higher education to adapt eBook technology more strategically to enhance the documentation of academic training and support a viable digital learning ecosystem.